2007
DOI: 10.1142/s0129065707001019
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Directionality of Coupling: Phase Versus State Space Dynamics and Application to Eeg Time Series

Abstract: Measuring the directionality of coupling between dynamical systems is one of the challenging problems in nonlinear time series analysis. We investigate the relative merit of two approaches to assess directionality, one based on phase dynamics modeling and one based on state space topography. We analyze unidirectionally coupled model systems to investigate the ability of the two approaches to detect driver-responder relationships and discuss certain problems and pitfalls. In addition we apply both approaches to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…48 Changes in spectral-coherence characteristics were revealed at all frequency bands, with maximal changes at 9 frequencies in drug addicts and in narrow-frequency a subranges in alcoholics. Ethanol and heroin consumers were characterized by different effects in the ¡3 band (19)(20)(21). Polysubstance abusers have been associated with reduced interhemispheric 5 and 0 bands, and frontal ¡3 band coherence.…”
Section: ~47mentioning
confidence: 99%
“…48 Changes in spectral-coherence characteristics were revealed at all frequency bands, with maximal changes at 9 frequencies in drug addicts and in narrow-frequency a subranges in alcoholics. Ethanol and heroin consumers were characterized by different effects in the ¡3 band (19)(20)(21). Polysubstance abusers have been associated with reduced interhemispheric 5 and 0 bands, and frontal ¡3 band coherence.…”
Section: ~47mentioning
confidence: 99%
“…This phase-modeling approach is based on the concept of phase synchronization ) between weakly coupled oscillators and was previously applied to intracranial EEG time series by Osterhage et al (2007). First, we extracted unwrapped phases from the preselected and prefiltered iEEG trials (4096 ms length) using wavelet transforms based on Morlet wavelets.…”
Section: Analysesmentioning
confidence: 99%
“…As a case study they apply these measures to EEG signals taken from one epilepsy patient during a seizure-free interval. 13 Adeli et al have shown that the wavelet transform was particularly effective for representing various aspects of non-stationary signals.…”
Section: -12mentioning
confidence: 99%